Breeding Biology of Red-throated Loons in the Canadian Beaufort Sea Region - Dickson, D. Lynne (ARCTIC, 1993)
The breeding biology of the red-throated loon in the Canadian Beaufort Sea region was investigated 1985 to 1989. Five study plots were established with a total area of 276 sq. km and over 200 pairs of loons on territory each breeding season. Loon densities ranged from 0.6 pairs/sq. km on the Yukon coast to 1.8 pairs/sq. km at Toker Point on the Tuktoyaktuk Peninsula. An average of 73% of the pairs on territory nested each year. Productivity averaged 0.63 young/nesting pair. The median date of egg laying ranged from 19 to 24 June in four years, but was 3 July in a year when spring thaw was late. The chicks fledged a mean of 47 d after hatch (n=10), the first clutch chicks leaving the nesting pond in late August to mid-September. In all but one year, the mortality rate was higher for eggs than chicks, with egg losses peaking in the second half of incubation. Most (82%) chick losses occurred within three weeks of hatch (n=61). Just 13% of the ponds were occupied in all five years of the study, while 39% were used in only one year. At two of the study plots, ponds with pairs that successfully reared at least one chick had a greater tendency to be occupied the following year than did ponds with unsuccessful pairs. At the other three plots, reuse of ponds was independent of breeding success the previous year.Key words: red-throated loon (Gavia stellata), breeding biology, Beaufort Sea On a étudié la reproduction du huart à gorge rousse dans la partie canadienne de la mer de Beaufort de 1985 à 1989. À chacune des périodes de reproduction, on a observé plus de 200 couples de huarts territoriaux répartis dans cinq zones expérimentales couvrant une superficie totale de 276 km². La densité des huarts a varié de 0.6 couple par km² sur la côte du Yukon à 1.8 couple par km² à Toker Point sur la péninsule de Tuktoyaktuk. Le nombre moyen annuel de couples nicheurs territoriaux s'est élevé à 73%. La productivité moyenne a été de 0.63 oisillon par couple nicheur. La date médiane de ponte s'est située ...